PENGARUH PENAMBAHAN UREA DAN MELAMIN PADA PEREKAT UREA FORMALDEHIDA TERHADAP EMISI FORMALDEHIDA DAN SIFAT FISIS-MEKANIS PAPAN PARTIKEL - Paribotro Sutigno; Adi Santoso (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
The formaldehyde emtsston of particleboard bonded with urea formaldehyde (UF) can affect health, especially if it is used in a room with limited ventilation. To reduce formaldehyde emission, the glue can be mixed with catching agent. In this report, the effect of using urea and melamine as catching agents on formaldehyde emission, and on the physical and mechanical properties of UF bonded particleboard is described.The effect of percentage of catching agent on formaldehyde emission is highly significant. The higher the percentage of catching agent, the lower formaldehyde emission of particleboard. On ureamelamine (U/M) ratio of 4, the formaldehyde emission of particleboard can meet American and Japanese Standard on the percentage of 5, 10 and 15%, while on U/M ratio of 7 and 10, the formaldehyde emission can conform the standards on the percentage of 10 and 15%. The effect of addition of urea and melamine was significant and even highly significant on the physical and mechanical properties, but not on the shear strength. The effect of U/M ratio was either not significant.Key words : particleboard, urea-melamine, formaldehyde emission, physical and mechanical properties.